Phonology is not accessed earlier than orthography in Chinese written production: evidence for the orthography autonomy hypothesis - Zhang, Qingfang; Wang, Cheng (Frontiers in Psychology, 2015)
The contribution of orthographic and phonological codes to written production remains controversial. We report results using a picture-word interference task in which participants were asked to write (Experiments 1 and 2) or to speak (Experiment 3) the names of pictures while trying to ignore visual distractors, and the interval between the target and distractor onset was varied. Distractors were orthographically plus phonologically related, orthographically related, phonologically related or unrelated to picture names. For written production, we found an exclusive orthographic effect at an early stage, reflecting a fast and direct link between meaning and graphemic lexicon, and we demonstrated that orthographic codes can be accessed directly from meaning in healthy adults. We also found orthographic and phonological effects at a later stage, reflecting a slow and indirect link between meaning and graphemic lexicon via phonology. Furthermore, the absence of an interaction effect of orthographic and phonological facilitation on written latencies suggests that the two effects are additive in general and that they might occur independently in written production in Chinese. For spoken production, we found that orthographic and phonological effects occur simultaneously in spoken production and that the two effects are additive at an early stage but interactive at a later stage. The temporal courses and their interplay of orthographic and phonological effects are dissociative in written and spoken production. Our findings thus support the orthography autonomy hypothesis, rather than the obligatory phonological mediation hypothesis, in written production in Chinese (as a non-alphabetic script).